دراسة الاستجابة الوراثية لبعض أصناف الحمص (Cicer arietinum L.) لتكوين الكالس أحادي الصيغة الصبغية مخبرياً - قبيلي صالح; معلا نزار; داؤد نبراس (Latakia University Journal -Biological Sciences Series, 2016)
أجري هذا البحث في مخبر زراعة الأنسجة بكلية الزراعة, جامعة تشرين, لما للحمص من أهمية غذائية واقتصادية كبيرة, حيث استخدم صنفان من الحمص الشتوي (غاب 4, غاب5) وصنفان ربيعيان ( ILC263, ILC1929 ) وزرعت في أصص حتى موعد الإزهار, حيث أخذت البراعم الزهرية قبل تفتحها و غسلت بالماء المقطر والكحول ثلاث مرات. تم فصل المتوك ومعاملتها بدرجات حرارة أولية (4 مْ لمدة 48 ساعة و 35 مْ لمدة 12 ساعة ) غسلت بعدها بمحلول هيبو كلوريت الصوديومNaocl 2% لمدة 15 دقيقة, بعدها غسلت بالماء المقطر المعقم حيث زرعت على بيئة موراشيج وسكوك MS المزودة بـ 1 و 3 و 5 ملغ/ل من أوكسين 2,4,D وكذلك 0.1 و 0.2 و 0.3 ملغ/ل من سيتوكينين بنزيل أمينو بيورينBAP كل على حدة وبالتفاعل بينهما وحضنت تحت ظروف 27 مْ و75 % من الرطوبة و شدة ضوئية 1500 لوكس لمدة 16 ساعة. كان الهدف الرئيس للبحث دراسة تأثير كل من المعاملة الحرارية الأولية ونوعية وتركيز الهرمون المستخدم على إنتاج كالس من متوك أصناف الحمص المستخدمة, بينت النتائج اختلاف الاستجابة الوراثية للأصناف للمعاملة الحرارية والهرمونية بشكل مفرد, حيث كان الصنف غاب 5 الأكثر استجابة لتكوين الكالس , بينما أشارت النتائج إلى أن أعلى نسبة لتكوين الكالس كانت 40% عند المعاملة بدرجة حرارة 4 مْ للصنف غاب 4 وغاب 5, في حين أن الصنف ILC263 أبدى أقل استجابة وفي جميع المعاملات المفردة لمنظمات النمو. أظهرت النتائج الدور الكبير والمحفز لاستخدام الهرمونين معاً مع المعاملة الحرارية, حيث تفوق كل من الأصناف غاب 5 و غاب 4 و ILC1929إذ بلغت النسبة إلى 80% و60% على التوالي. This research was conducted at the Laboratory of Tissue Culture, Faculty of Agriculture, Tishreen University. Because of the importance of the food and economic of chickpea, two Winter chickpea cultivars (Ghab 4, Ghab 5) and two Vernal chickpea cultivars were used (ILC263, ILC1929) and planted in pots until flowering, so the floral buds were picked before opened and washed with distilled water and alcohol three times. Anthers were separated and treated at preliminary temperatures (4 Cْ for 48 hours, and 35 Cْ for 12 hours), then it washed with a solution of hypochlorite of sodium( Naocl 2%) for a period of 15 minute, and washed with distilled sterilized water ,then where planted on the environment Murashige and Skoog ( MS) equipped with 1, 3 and 5 mg/L of auxin 2,4, D, as well as 0.1, 0.2 and 0.3 mg /L of Cytokinin Benzyl Amino Purine( BAP) individually and with interaction between them and incubated under conditions of 27 Cْ and 75% of the humidity and the intensity of 1500 Lux of light for 16 hours. The main objective of research was to study the effect of both preliminary heating treatment , quality and concentration of used hormone on producing callus from used chickpea cultivars anthers. Results showed difference in cultivars response in the treatment of both temperature and single hormone, so Ghab 5 cultivar was the most responsive to the formation of callus, while the results indicated that the highest percentage of the formation of callus was 40% when treated at 4 Cْ of Ghab 4 and Ghab 5 cultivars, while ILC263 cultivar showed less response in all the individual treatments for growth regulators. As well as results showed that the significant and catalyst role for using of hormones together with heat treatment, where each of Ghab 5, Ghab 4 and ILC1929 cultivars were the superiority, by the arrival of the percentage of 80% and 60%, respectively.